Zmieniający się kanon literatury amerykańskiej a kwestia amerykańskiej tożsamości: ponad pół wieku debat i kontrowersji - Dobosiewicz, Ilona (Er(r)go. Teoria - Literatura - Kultura, 2017)
[for abstract in Polish, scroll down] Ilona Dobosiewicz University of Opole The Changing Canon of American Literature and the Question of American Identity: Over Half a Century of Debates and Controversies Abstract: The article discusses the ways in which political and cultural revolution in the 1960s together with such social practices as university open admissions and affirmative action have changed the canon of American literature. It presents the factors that have led to the broadening of the canon and argues that the evolving canon of American literature no longer constructs a teleological meta-narrative of a unified tradition but instead reflects the ways in which multiple traditions and cultures engage in a dialog and influence one another. Keywords: literary theory, cultural theory Abstrakt: Artykuł omawia zmiany jakie zachodziły w postrzeganiu pojęcia kanonu literatury amerykańskiej w wyniku rewolucji politycznej i obyczajowej lat sześćdziesiątych ubiegłego wieku oraz takich praktyk społecznych jak uniwersytecka polityka otwartych drzwi i akcja afirmatywna. Pokazje jakie czynniki doprowadziły do rozszerzenia kanonu i wskazuje, że obecny kanon literatury amerykańskiej nie konstruuje już teleologicznej meta-narracji dotyczącej jednolitej tradycji, ale pokazuje w jaki sposób różnorakie tradycje i kltury wchodzą ze sobą w dialog i wzajemnie na siebie oddziaływują. Słowa klucze: teoria literatury, teoria kultury